Streptozotocin-Induced Hyperglycemia Affects the Pharmacokinetics of Koumine and its Anti-Allodynic Action in a Rat Model of Diabetic Neuropathic Pain - Ye, Li-Xiang; Huang, Hui-Hui; Zhang, Shui-Hua; Lu, Jing-Shan; Cao, Da-Xuan; Wu, Dan-Dan; Chi, Pei-Wang; Hong, Long-Hui; Wu, Min-Xia; Xu, Ying; Yu, Chang-Xi (Frontiers in Pharmacology, 2021)
Koumine (KM), the most abundant alkaloid in Gelsemium elegans, has anti-neuropathic, anti-inflammatory, and analgesic activities; thus, it has the potential to be developed as a broad-spectrum analgesic drug. However, factors determining the relationship between analgesic efficacy and the corresponding plasma KM concentration are largely unclear. The pharmacokinetics and pharmacodynamics of KM and their optimization in the context of neuropathic pain have not been reported. We investigated the pharmacokinetics and pharmacodynamics of KM after oral administration in a streptozotocin-induced rat model of diabetic neuropathic pain (DNP) using a population approach. A first-order absorption and elimination pharmacokinetics model best described the plasma KM concentration. This pharmacokinetic model was then linked to a linear pharmacodynamic model with an effect compartment based on the measurement of the mechanical withdrawal threshold. KM was rapidly absorbed (time to maximum plasma concentration: 0.14–0.34 h) with similar values in both DNP and naïve rats, suggesting that DNP did not influence the KM absorption rate. However, the area under the curve (AUC0-∞) of KM in DNP rats was over 3-fold higher than that in naïve rats. The systemic clearance rate and volume of KM distribution were significantly lower in DNP rats than in naïve rats. Blood glucose value prior to KM treatment was a significant covariate for the systemic clearance rate of KM and baseline value of the threshold. Our results suggest that streptozotocin-induced hyperglycemia is an independent factor for decreased KM elimination and its anti-allodynic effects in a DNP rat model. To the best of our knowledge, this is the first study to investigate the role of DNP in the pharmacokinetics and pharmacokinetics-pharmacodynamics of KM in streptozotocin-induced diabetic rats.